2017
DOI: 10.26804/ager.2017.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of reservoir pore/throat characteristics evolution during long-term waterflooding

Abstract: Formation pore structure and reservoir parameters change continually during waterflooding due to sand production, clay erosion, and pressure/temperature variation, which causes great challenge in geological modeling and simulation. In this work, the XA Oilfield, a block with more than 20 years' waterflooding history, is used as an example to better understand the fundamental evolution mechanisms of reservoir pore network characteristics over long time waterflooding. We performed a large number of core analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In accordance with the two-phase flow theory, the fluid-rock characters determine the relative permeability of each phase [26][27][28][29]. The functional relationship of the flow rate flowing into the th reservoir and the pressure can be obtained under the assumption of steady flow [27], or…”
Section: Calculation Methodmentioning
confidence: 99%
“…In accordance with the two-phase flow theory, the fluid-rock characters determine the relative permeability of each phase [26][27][28][29]. The functional relationship of the flow rate flowing into the th reservoir and the pressure can be obtained under the assumption of steady flow [27], or…”
Section: Calculation Methodmentioning
confidence: 99%
“…Therefore, the microfluidic models that better simulate the real pore structure are employed to observe the fingering phenomenon from micro insight to analyze the influence of various factors. The microfluidics can be made from various materials, such as glass, polydimethylsiloxane (PDMS), and polymethyl methacrylate (PMMA), performing different properties of simulated reservoirs as shown in Table .…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several studies have indicated that wettability alteration and pore structure variation are two important EOR mechanisms of high-PV displacement waterflooding [22][23][24][25][26]. Xiong et al [22] applied the contact angle to evaluate the wettability of rock during waterflooding and observed a shift in core wettability from oil-wet to intermediate-wet, which is beneficial for enhancing oil displacement efficiency [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%